Multiple paraovarian cysts requiring emergency surgery: A rare clinical finding. Issue 2 (6th February 2022) - Tominaga, Marie; Morikawa, Kyoko; Ogawa, Yutaro; Ishiguro, Hiromi; Kamimura, Naomi; Yokoo, Tomokazu; Tsuneki, Ikunosuke; Tamura, Masaki; Yanase, Toru; Kurabayashi, Takumi
Abstract: This report presents an unusual case of multiple paraovarian cysts that required emergency surgery due to a paraovarian cyst being entrapped by another paraovarian cyst. Laparoscopic surgery is considered useful for diagnostic and therapeutic purposes and is, therefore, recommended owing to difficulty in differentiating paraovarian cysts from ovarian cysts.